2013
DOI: 10.2478/s11756-013-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical amino acid residues for chloride binding of Bacillus licheniformis trehalose-6-phosphate hydrolase

Abstract: Based on sequence alignment of selected Cl − dependent and independent glycoside hydrolase family 13 enzymes, two invariant residues (Arg201 and Asn347) and one tyrosine (Tyr365) that might be responsible for the binding of Bacillus licheniformis trehalose-6-phosphate hydrolase (Bl TreA) to chloride ion were identified. The role of these three residues was further explored by mutational and biophysical analyses. The mutant enzymes (R201Q/E/K, N327Q/D/K, and Y365A/R) and Bl TreA were individually overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…3 From the results, we found a site Asn327 marked by a pentangle ( Figure 3 ). The site is considered essential for binding to chloride ions according to Ong et al (2014) . Moreover, the findings may help explain why TRE_P2 and TRE_P3 confer salt tolerance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 From the results, we found a site Asn327 marked by a pentangle ( Figure 3 ). The site is considered essential for binding to chloride ions according to Ong et al (2014) . Moreover, the findings may help explain why TRE_P2 and TRE_P3 confer salt tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the considerable amount of negatively charged acid residues dispersed on the outer layer of the protein may also play a part in it as it constituted a solvation case, preventing the protein layer from dehydrating and helping the protein adapt salinity (De Santi et al, 2016;Wang et al, 2016). Ong et al (2014) also found out that the efficiency of BlTreA and Y365A enzymes toward pNPG was limited when they were desalted, maintaining less than 15.8% of the TreA activity. Given this salt-tolerance property, rTRE_P2 and rTRE_P3 are useful for reporter genes (Sniezko et al, 1998) and other salttolerant environments.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations